Revealing the Role of Hydrogen in Highly Efficient Ag-Substituted CZTSSe Photovoltaic Devices: Photoelectric Properties Modulation and Defect Passivation - Zhao, Xiaoyue; Li, Jingru; Hu, Chenyang; Qi, Yafang; Zhou, Zhengji; Kou, Dongxing; Zhou, Wenhui; Yuan, Shengjie; Wu, Sixin (Nano-Micro Letters, 2024)
The presence of SnZn-related defects in Cu2ZnSn(S,Se)4 (CZTSSe) absorber results in large irreversible energy loss and extra irreversible electron–hole non-radiative recombination, thus hindering the efficiency enhancement of CZTSSe devices. Although the incorporation of Ag in CZTSSe can effectively suppress the SnZn-related defects and significantly improve the resulting cell performance, an excellent efficiency has not been achieved to date primarily owing to the poor electrical-conductivity and the low carrier density of the CZTSSe film induced by Ag substitution. Herein, this study exquisitely devises an Ag/H co-doping strategy in CZTSSe absorber via Ag substitution programs followed by hydrogen-plasma treatment procedure to suppress SnZn defects for achieving efficient CZTSSe devices. In-depth investigation results demonstrate that the incorporation of H in Ag-based CZTSSe absorber is expected to improve the poor electrical-conductivity and the low carrier density caused by Ag substitution. Importantly, the C=O and O–H functional groups induced by hydrogen incorporation, serving as an electron donor, can interact with under-coordinated cations in CZTSSe material, effectively passivating the SnZn-related defects. Consequently, the incorporation of an appropriate amount of Ag/H in CZTSSe mitigates carrier non-radiative recombination, prolongs minority carrier lifetime, and thus yields a champion efficiency of 14.74%, showing its promising application in kesterite-based CZTSSe devices. Highlights: 1 The Ag/H co-doping strategy has been proposed to promote the performance of Cu2ZnSn(S,Se)4 (CZTSSe) devices. 2 The incorporation of H in Ag-based CZTSSe photovoltaic absorber is expected to improve the poor electrical conductivity and the low carrier density caused by Ag substitution. 3 Benefiting from the synergism of the excellent defect passivation effect and photoelectric properties complementary effect enabled by Ag/H co-doping, a champion device with 14.74% efficiency is achieved.